Responses of tidal dynamic and water exchange capacity to coastline change in the Bohai Sea, China - Wu, Zhengcheng; Zhou, Chunyan; Wang, Peng; Fei, Zihao (Frontiers in Marine Science, 2023)
Bohai Sea (BHS) is a semi-enclosed shallow continental sea in China that has suffered from the deteriorative hydrodynamic environment and material transport due to large-scale reclamation. The tidal dynamic and water exchange capacity of BHS were investigated by a verified numerical model. Single-factor simulations of tidal currents and material transport under the influence of the coastline changes from 1999 to 2019 in BHS were carried out. The model results show that the amplitude of M2 tide increased slightly in Liaodong Bay and Bohai Bay, but decreased obviously in Laizhou Bay along with larger reclamation scale. The amplitude variation of the semi-diurnal constituents (M2, S2) was greater than the diurnal ones (K1, O1). The area of three bays in BHS shrank by similar proportions from 1999 to 2019, while the tidal prism in Liaodong Bay and Laizhou Bay decreased by 1.01% and 7.79%, respectively. The tidal prism is highly related to the residence time. The basin residence time in Liaodong Bay and Laizhou Bay increased by 5.44% and 49.44% from 1999 to 2019, respectively. Runoff of the Huanghe River can shorten the residence time of Laizhou bay while only has little effect on Bohai Bay and Liaodong Bay. Longer residence time indicates weaker water exchange capacity. The study of the Bohai Sea evolution can provide recommendations for subsequent marine ecological restoration efforts and serve as a reference for the study of other large semi-enclosed bays.